The Effect of Maternal Separation on Anxiety Behavior in of White Mice (Mus Musculus L.) Male Swiss Webster Strain - Budi Santoso; Siti Sarahdeaz Fazzaura Putri; Eka Febri Zulissetiana; Alfian Hasbi; Alvita Putri Luthfiyyah; Nada Triastuti (Fakultas Kedokteran Universitas Sriwijaya, 2026)
Introduction. Maternal separation (MS) is a commonly utilized model of early-life stress to explain the influence on brain development and psychological behavior. MS has been demonstrated to elevate the likelihood of developing anxiety disorders as a consequence of alterations in hypothalamic- pituitary-adrenal (HPA) functionality and neurotransmitter levels. This study aimed to evaluate the impact of maternal separation (MS) duration on anxiety behavior in male Swiss Webster strain white mice (Mus musculus L.). Methods. The study used a true experimental method with a posttest- only control group design. A total of 28 male mice aged 2 days were randomly assigned to one of four groups: a control group that did not undergo maternal separation (MS) and three MS treatment groups with a duration of 2 hours, 4 hours, and 6 hours per day for 21 days. Anxiety behavior was evaluated using the Elevated Plus Maze (EPM), with the number and duration of entries into the closed and open arms serving as the primary analysis metrics. The data were analyzed using one-way ANOVA and post-hoc LSD statistical tests. The duration of MS significantly impacted the anxiety behavior of the mice. Results. The MS groups of 2, 4 and 6 hours demonstrated a notable increase in the number and duration of entries into the closed arm in comparison to the control group (p < 0.05), which is indicative of increased anxiety. In contrast, the number of entries into the open arm decreased in the 6 h MS group compared to the control. Conclusion. The results indicated that MS negatively affected the anxiety behavior of mice, with longer duration exacerbating the trend.